Current and future applications of brain magnetic resonance imaging in ARSACS - Alessandra Scaravilli; Davide Negroni; Claudio Senatore; Filippo Maria Santorelli; Sirio Cocozza (The Cerebellum, 2025)
Magnetic Resonance Imaging (MRI) is a tool with an unquestionable role in the study of neurodegenerative disorders, both for diagnostic purposes and for its ability of providing imaging-derived biomarkers with a growing central role as reliable outcomes in clinical trials. This is even more relevant when dealing with rare disorders such as the Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS), in which the search of diagnostic and prognostic biomarker is crucial. Due to the rarity of this condition, a comprehensive knowledge of MRI signs observed in ARSACS is lacking. Furthermore, many domains remain still unexplored in ARSACS, especially with reference to the application of advanced imaging techniques that could shed light on the pathophysiological mechanisms of brain damage in this disorder. In this review, after a brief introduction on the major conventional and advanced MRI techniques that can used for diagnostic and research purposes, we present current neuroradiological knowledge in ARSACS. Having discussed strength and weak points of conventional and advanced imaging findings, we also suggest possible future research in this neurologically complex clinical condition.

Altered Intracerebellar Functional Connectivity in Friedreich’s Ataxia: A Graph-Theory Functional MRI Study - Mario Tranfa; Teresa Costabile; Giuseppe Pontillo; Alessandra Scaravilli; Chiara Pane; Arturo Brunetti; Francesco Saccà; Sirio Cocozza (The Cerebellum, 2025)
Historically, Friedreich’s Ataxia (FRDA) has been linked to a relatively preserved cerebellar cortex. Recent advances in neuroimaging have revealed altered cerebello-cerebral functional connectivity (FC), but the extent of intra-cerebellar FC changes and their impact on cognition remains unclear. This study investigates intra-cerebellar FC alterations and their cognitive implications in FRDA. In this cross-sectional, single-center study, resting-state functional MRI data from 17 patients with FRDA (average age 27.7 ± 13.6 years; F/M = 6/11) and 20 healthy controls (HC) (average age 29.4 ± 9.7 years; F/M = 9/11), all of whom underwent neuropsychological testing, were analyzed. From functional connectivity matrices, graph measures were computed at both the network and node levels using two complementary parcellations. FRDA patients exhibited decreased global efficiency ( p = 0.04), nodal degree ( p = 0.001) and betweenness centrality ( p = 0.04) in the vermal portion of lobule VIII, along with reduced global efficiency in cerebellar regions belonging to the Control-A network ( p = 0.02), one of the three subdivisions of the Frontoparietal network. Verbal memory deficits correlated with global efficiency in both the vermal portion of lobule VIII ( r = 0.53, p = 0.02) and the cerebellar regions of the Control-A network ( r = 0.49, p = 0.05). Graph analysis revealed regional intra-cerebellar FC changes in FRDA, marked by reduced functional centrality in cerebellar regions of the vermis and responsible for executive functions. These changes correlated with cognitive alterations, highlighting the role of the cerebellar cortex in the cognitive impairment observed in FRDA.

CHARON: An Imaging-Based Diagnostic Algorithm to Navigate Through the Sea of Hereditary Degenerative Ataxias - Alessandra Scaravilli; Mario Tranfa; Giuseppe Pontillo; Bernard Brais; Giovanna De Michele; Roberta La Piana; Francesco Saccà; Filippo Maria Santorelli; Matthis Synofzik; Arturo Brunetti; Sirio Cocozza (The Cerebellum, 2024)
The complexity in diagnosing hereditary degenerative ataxias lies not only in their rarity, but also in the variety of different genetic conditions that can determine sometimes similar and overlapping clinical findings. In this light, Magnetic Resonance Imaging (MRI) plays a key role in the evaluation of these conditions, being a fundamental diagnostic tool needed not only to exclude other causes determining the observed clinical phenotype, but also to proper guide to an adequate genetic testing. Here, we propose an MRI-based diagnostic algorithm named CHARON (Characterization of Hereditary Ataxias Relying On Neuroimaging), to help in disentangling among the numerous, and apparently very similar, hereditary degenerative ataxias. Being conceived from a neuroradiological standpoint, it is based primarily on an accurate evaluation of the observed MRI findings, with the first and most important being the pattern of cerebellar atrophy. Along with the evaluation of the presence, or absence, of additional signal changes and/or supratentorial involvement, CHARON allows for the identification of a small groups of ataxias sharing similar imaging features. The integration of additional MRI findings, demographic, clinical and laboratory data allow then for the identification of typical, and in some cases pathognomonic, phenotypes of hereditary ataxias.

The role of unidentified bright objects in the neurocognitive profile of neurofibromatosis type 1 children: a volumetric MRI analysis - Martina Di Stasi; Sirio Cocozza; Sara Buccino; Chiara Paolella; Linda Di Napoli; Alessandra D’Amico; Daniela Melis; Lorenzo Ugga; Gianmichele Villano; Manuel Ruocco; Iris Scala; Arturo Brunetti; et al. (Acta Neurologica Belgica, 2024)
Purpose Cognitive impairment is described in 80% of Neurofibromatosis type 1 (NF1) patients. Brain focal areas of T2w increased signal intensity on MRI, the so-called Unidentified Bright Objects (UBOs) have been hypothesized to be related to cognitive dysfunction, although conflicting results are available in literature. Here, we investigated the possible relation between UBOs’ volume, cognitive impairment, and language disability in NF1 patients. Material and methods In this retrospective study, clinical and MRI data of 21 NF1 patients (M/F = 12/9; mean age 10.1 ± 4.5) were evaluated. Brain intellectual functioning and language abilities were assessed with specific scales, while the analyzed MRI sequences included axial 2D-T2-weighted and FLAIR sequences. These images were used independently for UBOs segmentation with a semiautomatic approach and obtained volumes were normalized for biparietal diameters to take into account for brain volume. Possible differences in terms of normalized UBOs volumes were probed between cognitively affected and preserved patients, as well as between subjects with or without language impairment. Results Patients cognitively affected were not different in terms of UBOs volume compared to those preserved ( p = 0.35 and p = 0.30, for T2-weighted and FLAIR images, respectively). Similarly, no differences were found between patients with and without language impairment ( p = 0.47 and p = 0.40, for the two sequences). Conclusions The relation between UBOs and cognition in children with NF1 has been already investigated in literature, although leading to conflicting results. Our study expands the current knowledge, showing a lack of correlation between UBOs volume and both cognitive impairment and language disability in NF1 patients.

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

A Review of Brain and Pituitary Gland MRI Findings in Patients with Ataxia and Hypogonadism - Alessandra Scaravilli; Mario Tranfa; Giuseppe Pontillo; Bernard Brais; Giovanna De Michele; Roberta La Piana; Francesco Saccà; Filippo Maria Santorelli; Matthis Synofzik; Arturo Brunetti; Sirio Cocozza (The Cerebellum, 2023)

Ataxia and Hypogonadism: a Review of the Associated Genes and Syndromes - Giovanna De Michele; Luigi Maione; Sirio Cocozza; Mario Tranfa; Chiara Pane; Daniele Galatolo; Anna De Rosa; Giuseppe De Michele; Francesco Saccà; Alessandro Filla (The Cerebellum, 2023)

NO-HYPE: a novel hydrodynamic phantom for the evaluation of MRI flow measurements - Giacomo Gadda; Sirio Cocozza; Mauro Gambaccini; Angelo Taibi; Enrico Tedeschi; Paolo Zamboni; Giuseppe Palma (Medical & Biological Engineering & Computing, 2021)
Accurate and reproducible measurement of blood flow profile is very important in many clinical investigations for diagnosing cardiovascular disorders. Given that many factors could affect human circulation, and several parameters must be set to properly evaluate blood flows with phase-contrast techniques, we developed an MRI-compatible hydrodynamic phantom to simulate different physiological blood flows. The phantom included a programmable hydraulic pump connected to a series of pipes immersed in a solution mimicking human soft tissues, with a blood-mimicking fluid flowing in the pipes. The pump is able to shape and control the flow by driving a piston through a dedicated software. Periodic waveforms are used as input to the pump to move the fluid into the pipes, with synchronization of the MRI sequences to the flow waveforms. A dedicated software is used to extract and analyze flow data from magnitude and phase images. The match between the nominal and the measured flows was assessed, and the scope of phantom variables useful for a reliable calibration of an MRI system was accordingly defined. Results showed that the NO-HYPE phantom is a valuable tool for the assessment of MRI scanners and sequence design for the MR evaluation of blood flows. Graphical abstract

Functional MRI signal fluctuations highlight altered resting brain activity in Huntington’s disease - Chiara Sarappa; Elena Salvatore; Alessandro Filla; Sirio Cocozza; Cinzia Valeria Russo; Francesco Saccà; Arturo Brunetti; Giuseppe De Michele; Mario Quarantelli (Brain Imaging and Behavior, 2017)